2017
DOI: 10.1002/hed.24822
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for olfactory neuroblastoma treated with induction chemotherapy

Abstract: ONB is a chemosensitive tumor and induction chemotherapy is an acceptable strategy for aggressive and locoregional advanced disease. Hyams grade may predict chemosensitivity and CR may be associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 32 publications
2
59
2
1
Order By: Relevance
“…The characteristics of ONB and non‐ONB head and neck NSCCs can differ substantially . Accordingly, we compared clinical results between ONB ( n = 5) and non‐ONB ( n = 30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of ONB and non‐ONB head and neck NSCCs can differ substantially . Accordingly, we compared clinical results between ONB ( n = 5) and non‐ONB ( n = 30).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of ONB and non-ONB head and neck NSCCs can differ substantially. (12)(13)(14) Accordingly, we compared clinical results between ONB (n = 5) and non-ONB (n = 30). The 3-year local control rates for ONB and non-ONB were 100% and 92%, respectively (P = 0.41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, chemotherapy is recommended in cases of high‐grade and positive margins tumors, unresectable tumors, metastatic disease, and relapses . Response rate to neoadjuvant chemotherapy is higher in a Hyams high‐grade group compared to a Hyams low‐grade group, 78% versus 50%, respectively . Furthermore, Polin et al showed that patients with a response to neoadjuvant therapy with chemotherapy and/or RT have a significant lower rate of disease‐related mortality .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Chemotherapy might be used in case of high-grade, recurrent, or locoregionally advanced tumors. [17][18][19] In pediatric cases, chemotherapy combined with surgery and radiotherapy (RT) is often the treatment of choice in advanced diseases compared to adult ones. 3,6 The incidence of cervical node metastases is about 10% at diagnosis but can increase to 20% during the disease in adults.…”
mentioning
confidence: 99%